Medical Images in Integrated Health Care Workstations - Meinzer, H-P.; Engelmann, U. (Yearbook of Medical Informatics, 1996)
The difference between an invention and a discovery is discussed, before turning to the sources of medical images. Next, the ongoing integration of image modalities in clinical routine is reviewed, as well as improvements in diagnosis and therapy planning with the help of better images in inter-connected distributed systems. Current shortcomings of image processing, and the attempts to overcome these shortcomings are presented. Examples of image processing are given, together with a vision on future systems and procedures.
Keywords: Imaging; Image Processing; Workstations; Integration